Transmissible parasitic zoonoses of the Kaluga Region - F. I. Vasilevich; A. M. Nikanorova (Российский паразитологический журнал, 2020)
the purpose of the research is monitoring population and species composition of common blood-sucking ectoparasites of the Kaluga Region, mosquitoes and ixodid ticks, and parasitic zoonoses, in the circulation of which they are involved.Materials and methods. The records were made in all districts of the Kaluga Region and in the city of Kaluga. We studied open meadow-field and forest-shrub stations, closed meadow-field and near-water stations, and settlement stations. The species was identified using the atlases of ixodid ticks by I. M. Ganiev, A. A. Aliverdiev (1968) and V. N. Shevkoplyas (2008), and the guidance of R. M. Gornostaeva (1999). The situation with transmissible parasitic zoonoses in the Kaluga Region was assessed based on the analysis of information from open sources of the Hygienic and Epidemiological Center of the Kaluga Region and the Veterinary Committee under the Government of the Kaluga Region.Results and discussion. There are two species of ixodid ticks in the Kaluga region: Ixodes ricinus and Dermacentor reticulatus. The abundance index of ixodid ticks of the species I. ricinus is 16.8±1.32 individuals per 1 flag-hour in forest biotopes, and 11.6±1.12 individuals per 1 flag-hour in meadow biotopes, and the abundance index of D. reticulatus is 10,8±1.14 and 15.9±1.30 individuals per 1 flag-hour, respectively. Three mosquito species prevail, namely, Stegomya communis, S. vexans, and Culex pipiens. The maximum number was 8 thousand per 1 m3. During the study period, the causative agent of infectious tick-borne borreliosis was found on average in 10.6% of ixodid ticks collected from humans and in 13.2% of ticks collected in natural biotopes. The causative agent of human granulocytic anaplasmosis was isolated on average in 3.1% of ixodid ticks collected from humans and 6.4% of those collected in natural biotopes. Infection rate for I. ricinus ticks infected with pathogen of infectious tick-borne borreliosis was 16.9%, and D. reticulatus 12.3%.